Civil Society in Transition: The Case of Germany in the Field of Education - Jana Priemer (Nonprofit Policy Forum, 2024)
The field of education has undergone a profound transformation in recent decades due to shifts in public governance in numerous Western countries. This transformation has been particularly evident in the realm of civil society organizations (CSOs) operating in the education sector. This article illustrates this phenomenon in the context of Germany, where education has evolved into a quantitatively significant and highly diversified field of CSO activities within a relatively brief period of three decades. The study is based on the theoretical assumption that the flourishing of CSOs depends on conditions set by the government. It follows that changing educational governance has led not only to the prospering of civil society but also to structural changes of CSOs in the field of education. Therefore, it outlines the main developments in educational governance in Germany that resulted in increased collaboration between CSOs and schools. Analyses of a dataset of 6,334 German CSOs demonstrate that the field of CSOs in education is currently pluralized and diverse, comprising service providers, support organizations, and advocacy organizations. New collaborations between CSOs and the state result in the adaptation of these organizations to new tasks and professionalization. Nevertheless, CSOs representing a novel type of civil society actor have also emerged. This article contributes to a broader discussion of structural change in civil society in the context of new public governance.
Keywords: 320